Using telecasting to identify turn times in alpine skiing - Swaren, M.; Larsson, O.; Björklund, G. (Journal of Human Sport & Exercise, 2017)
Alpine skiing can be considered as a "closed sport" where each athlete is alone in the course without any external disturbing moments. However, each alpine race is unique therefore never identical. In addition, the condition of the course is constantly changing as each skier makes new tracks in the snow. Identifying key performance indicators (KPI) and other characteristics are therefore difficult. The most frequently used analysis method in alpine skiing is video footage. However, it is not always possible for coaches to cover a complete course as they can be several kilometers long as e.g. downhill skiing. The purpose of this study was thus to explore the possibility to use telecasting to analyze performance and skiing characteristics in world cup slalom races to identify possible KPI. Slalom races (men) from the 2014/2015 season were analyzed by two separate video analysts, at two different occasions. One analyst was a professional performance analysist in sports and the other analyst is a slalom ski coach. Standard telecasting footage from the races was for analyzing the turn times for the nine best racers. Typical error (TE) was calculated by; ... The standardized typical error (STE) was calculated by; ... The official race results were downloaded for all men world cup slalom races from the 2011/2012 season. Race times for the first and second runs were divided by the number of turns in each run. TE between the two analysts was 0.03 s and STE was 0.14. The fastest mean turn time was from the 2011/2012 season, 0.819 ± 0.027 s whereas the corresponding time for "slowest" season (2013/2014) was 0.849 ± 027 s. There are clear differences in turn times between skiers, races and seasons. The STE was 0.13 which is below 0.2 and can hence be considered as trivial. The value of the TE (0.03 s) is most likely due to the framerate of the telecasting which is 25 fps. Each frame is hence 0.04 s and the analysts must choose one frame if the point of interest is between two frames. TE will presumably decrease with increase framerate. The combination of using official race results together with individual turn time analysis from telecasting footage provides a robust, cheap and effective method to objectively analyze skiing performance and identifying KPI. The results can also be used by coaches as an objective method to analyze skiing performance during training and also the quality of the training.